2017
DOI: 10.1080/02331888.2016.1277225
|View full text |Cite
|
Sign up to set email alerts
|

The shapes of things to come: probability density quantiles

Abstract: For every discrete or continuous location-scale family having a square-integrable density, there is a unique continuous probability distribution on the unit interval that is determined by the density-quantile composition introduced by Parzen in 1979. These probability density quantiles (pdQ s) only differ in shape, and can be usefully compared with the Hellinger distance or Kullback-Leibler divergences. Convergent empirical estimates of these pdQ s are provided, which leads to a robust global fitting procedure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…When the density function f is bounded, we showed that each application lowers its modal height and hence the resulting density function is closer to the uniform density than f . Furthermore, we established a necessary and sufficient condition for converging in norm to the uniform density, giving a positive answer to a conjecture raised in [ 1 ]. In particular, if f is bounded, we proved that converges in norm to the uniform density for any .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…When the density function f is bounded, we showed that each application lowers its modal height and hence the resulting density function is closer to the uniform density than f . Furthermore, we established a necessary and sufficient condition for converging in norm to the uniform density, giving a positive answer to a conjecture raised in [ 1 ]. In particular, if f is bounded, we proved that converges in norm to the uniform density for any .…”
Section: Discussionmentioning
confidence: 68%
“…It is known that the Tukey( ) distributions, with , are good approximations to Student’s t -distributions for provided is chosen properly. The same is true for their corresponding pdQs ([ 1 ], Section 3.2). For example, the pdQof with degrees of freedom is well approximated by the choice Its location is marked by the small black disk in Figure 1 ; it is of distance 2 from uniformity.…”
Section: Divergences Between Probability Density Quantilesmentioning
confidence: 79%
See 2 more Smart Citations
“…Dedduwakumara et al (2019) introduced a method for choosing optimal parameters for generalized distributions to approximate other distributions. The method uses the probability density quantile function (pdQ, Staudte, 2017) to first find the optimal shape parameters and is computationally quick, simple to implement and often outperforms other methods. Motivated by this, we introduce estimators of the GLD shape parameters arising from the estimated pdQ.…”
Section: Introductionmentioning
confidence: 99%